Ὰ la guerre comme à la guerre: a Look at Lithuanian Public War Discourse - Papaurėlytė-Klovienė, Silvija (Acta humanitarica academiae Saulensis, 2019)
The aim of the present paper is to compare the specificity of war discourse actualized in the magazine KARYS of the July issues of the 1937 and 2017 years. In order to achieve this aim, the following objectives have been set: to define the limits of public war discourse; to classify the conceptual metaphors actualized in the texts; to summarize the most important concepts described in the texts; on the basis of the obtained results to make assumptions what world view is created in the issues of the magazine KARYS of different years. War discourse refers to the everyday life of the armed forces, military technology, military conflicts, people’s (un)willingness to fight for their homeland with a weapon and under threat of death, and thus values, moral choices and other topics that are fully revealed by conceptualizing metaphors. The implied target audience and the nature of the message conveyed to it can essentially change transferable features while actualizing a metaphor. After classifying and analysing the conceptual metaphors actualized in the magazine KARYS in the July issues of 1937 and 2017 years, it was revealed that they are universal, however, they differ in a variety of transferred features. The differences can be attributed to the particularities of the non-linguistic reality: since 1937, from an independent state, which was essentially a land of farmers, it was switched to the advanced state which has industry and developed technologies. All these factors are actualized in the metaphors of the relevant period. Some of the topics covered in both issues of the journal are common: it is written about the excellent preparation of Lithuanian soldiers, the troubled international situation is mentioned as well. The topics of the 2017 issue can be described as more realistic and the world view is described as more dramatic and gloomy.